The Meaning of Tragic in Contemporary Performance (Itinera, 2016)
In this interview Carmelo Rifici spellsout thedifferentmeanings that tragic acquiresin his performances and reflectson its implications in the work of the actor. Particular attention is given to the relationship that the latter establishes with the originalsource s/he is asked to perform.